Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1103/physrevd.93.105028
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Maxwell equations for inhomogeneous chiral plasma

Abstract: Using the chiral kinetic theory we derive the electric and chiral current densities in inhomogeneous relativistic plasma. We also derive equations for the electric and chiral charge chemical potentials that close the Maxwell equations in such a plasma. The analysis is done in the regimes with and without a drift of the plasma as a whole. In addition to the currents present in the homogeneous plasma (Hall current, chiral magnetic, chiral separation, and chiral electric separation effects, as well as Ohm's curre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 65 publications
3
99
0
Order By: Relevance
“…[47,55] and both studies concluded that inhomogeneities of the chiral asymmetry have a negligible role for the primordial plasma. Moreover, it was demonstrated in [47] that the inverse cascade proceeds practically in the same way as in the chirally homogeneous model. This assumption can therefore be taken as justified, especially since our main concern in this work is the interplay between the anomaly induced and MHD inverse cascade.…”
Section: Modified Mhd Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[47,55] and both studies concluded that inhomogeneities of the chiral asymmetry have a negligible role for the primordial plasma. Moreover, it was demonstrated in [47] that the inverse cascade proceeds practically in the same way as in the chirally homogeneous model. This assumption can therefore be taken as justified, especially since our main concern in this work is the interplay between the anomaly induced and MHD inverse cascade.…”
Section: Modified Mhd Equationsmentioning
confidence: 99%
“…Some of these objects such as core collapse supernovae, reach high temperatures which makes studies of the chiral magnetic effect in such objects and in the early Universe technically similar. In [46] the formalism was extended to the case of spatially dependent µ 5 , and in [47] it was demonstrated that these inhomogeneities do not prevent the anomalydriven inverse cascade. Again, in all the approaches it was assumed that there are no velocity fields and therefore no turbulence occurring, although even some simple estimates seem to show that it could play a potentially important role both in the early universe [17,38] and in neutron stars [43].…”
Section: Introductionmentioning
confidence: 99%
“…(37), (38), and (39) into Eqs. (25), (29), and (30), respectively, and performing the integral over t with assumingn 5 (∞) = 0 in the first, 5 we havē…”
Section: E Physical Consequencesmentioning
confidence: 99%
“…(38) and (39)] and the scaling laws of the magnetic and kinetic correlation lengths in chiral matter [see Eqs. (47), (48), and (59)].…”
Section: Introductionmentioning
confidence: 99%
“…This contribution to the electric current causes an instability in the system (Joyce & Shaposhnikov 1997) that has been analyzed in many works (Fröhlich & Pedrini 2000;Ooguri & Oshikawa 2012;Boyarsky et al 2012a;Kumar et al 2014;Grabowska et al 2015;Manuel & Torres-Rincon 2015;Buividovich & Ulybyshev 2016;Boyarsky et al 2015;). This instability may be relevant in the physics of the early universe (Joyce & Shaposhnikov 1997;Fröhlich & Pedrini 2000, 2002Semikoz & Sokoloff 2004;Semikoz et al 2009;Boyarsky et al 2012a,b;Semikoz et al 2012;Tashiro et al 2012;Dvornikov & Semikoz 2012, 2014Manuel & Torres-Rincon 2015;Gorbar et al 2016;Pavlović et al 2016;Pavlović et al 2017), of the quark-gluon plasmas (Akamatsu & Yamamoto 2013;Taghavi & Wiedemann 2015;Hirono et al 2015), or of neutron stars (Ohnishi & Yamamoto 2014;Dvornikov & Semikoz 2015a,b;Yamamoto 2016;Dvornikov 2016). However, to the best of our knowledge, a systematic analysis of the system of chiral MHD equations, including the back-reaction of the magnetic field on the chiral chemical potential and the coupling to the plasma velocity field, U (t, x) appears to be missing.…”
Section: Introductionmentioning
confidence: 99%